Faktor-Faktor yang Berpengaruh terhadap Kepuasan Kerja di PT. Perkebunan Nusantara IX Batujamus Karanganyar - Fitriani, Fitriani; Widiastuti, Tantri (Jurnal Ilmiah Aset, 2012)
The objective of this research was to find out the influence of individual factor, social factor and primary factor in work toward work satisfaction at PT Perkebunan Nusantara IX Batujamus/Kerjoarum Karanganyar. The population in this research was entire employees counted as 1750 employees at PT Perkebunan Nusantara IX Batujamus/Kerjoarum Karanganyar. The samples were 95 respondents. The technique sampling that was used in this research was purposive sampling. The analysis instrument used in this research was multiple linear regression. The research result showed that there was significant influence of individual factor, social and primary factor in work toward job satisfaction at PT Perkebunan Nusantara IX Batujamus Karanganyar. The partial research result showed that individual factors influence the job satisfaction of employees of PT. Perkebunan Nusantara IX Batujamus Karanganyar. Social factors also influence the job satisfaction of employees of PT. Perkebunan Nusantara IX Batujamus Karanganyar and primary factor in work towards job satisfaction at PT Perkebunan Nusantara IX Batujamus Karanganyar.